Critical Synthesis Package: Physician Values in Practice Scale (PVIPS) - Christie Palladino (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Physician Values in Practice Scale (PVIPS), (2) a copy of the PVIPS instrument, scoring key and PVIPS manual developed by Paul Hartung, PhD. The PVIPS is a 60-item measure of work values specific to medical practice, containing six subscales of Prestige, Service, Autonomy, Lifestyle, Management, and Scholarly Pursuits. Originally developed for use by medical students, it has also been used with samples of residents and practicing physicians, and has been adopted by the Association of American Medical Colleges' Careers in Medicine program to assist medical students in understanding the ways in which work values relate to career choice. Responses on the PVIPS demonstrate adequate interitem reliability, and differences in work values profiles, as measured by the PVIPS, have been found in multiple samples across a range of specialties. The difference in value profiles among students selecting different specialties has been confirmed in multiple studies. These differences seem consistent in students from both allopathic and osteopathic schools of medicine, but are relatively small in magnitude. However, further research is needed to evaluate the potential applicability of the PVIPS to clinicians and students in other health science disciplines. Finally, it should be noted that a relative disadvantage of the measure is its length. While a short form of the PVIPS has been developed and validated in an Australian sample, we need further research to evaluate its psychometric properties in multiple other samples of medical students and physicians.